2006
DOI: 10.1200/jco.2005.03.9289
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Relationship of Patient Age and Paclitaxel Clinical Pharmacology: Cancer and Leukemia Group B (CALGB 9762)

Abstract: Although paclitaxel CL(tb) decreases with increasing patient age, there is great interpatient variability. Cooperative group studies to evaluate the effect of aging on pharmacokinetics are feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 32 publications
2
55
0
Order By: Relevance
“…A prospective trial by the Cancer and Leukemia Group B (CALGB 9762) demonstrated age-related differences in the pharmacokinetics of paclitaxel but no significant adverse sequelae in terms of infections and hospitalization. However, this trial analysed only the first cycle of treatment and cumulative toxicity was not assessed [Lichtman et al 2006]. An increased cardiovascular toxicity was reported in a prospective study of qw paclitaxel in 46 elderly patients with MBC; the baseline geriatric assessment predicted a lower probability of response and survival but not of toxicity [Del Mastro et al 2005].…”
Section: Elderly Patients With Metastatic Breast Cancermentioning
confidence: 99%
“…A prospective trial by the Cancer and Leukemia Group B (CALGB 9762) demonstrated age-related differences in the pharmacokinetics of paclitaxel but no significant adverse sequelae in terms of infections and hospitalization. However, this trial analysed only the first cycle of treatment and cumulative toxicity was not assessed [Lichtman et al 2006]. An increased cardiovascular toxicity was reported in a prospective study of qw paclitaxel in 46 elderly patients with MBC; the baseline geriatric assessment predicted a lower probability of response and survival but not of toxicity [Del Mastro et al 2005].…”
Section: Elderly Patients With Metastatic Breast Cancermentioning
confidence: 99%
“…The potential of natural products from plants, notably from traditional Chinese medicine (TCM), has been recognized by the scientific community in the Western world for its low toxicity, and considerable efforts have been made to systematically investigate the active component of TCM for cancer therapy. A series of natural products, such as Homoharringtonine (6), arsenic trioxide (ATO) (7) and paclitaxel (8), have been found and clinically proved for their potential use in leukemia therapy. They demonstrate the translation of basic knowledge of purified agents of complex mixtures from TCM into the clinic.…”
Section: Introductionmentioning
confidence: 99%
“…With higher age, there was an increase in the area under the curve (AUC) of paclitaxel and a decrease in drug clearance. This translated into an age-related increase in grade 3 neutropenia and lower absolute neutrophil count (ANC) nadir; however, there was no increase in the incidence of fever, hospitalisation, or need for intravenous antibiotics (Lichtman et al, 2006). Common comorbid medical conditions in older adults may impact tolerance to cancer therapy.…”
Section: Taxanesmentioning
confidence: 99%